KAJIAN LITERATUR PENDIDIKAN YANG MEMANUSIAKAN MANUSIA: SUDAHKAH TERWUJUD - Ummi Nur Aini; Nadia Hafiza Zahra; Nabilah Shafa Kamilah Dewi; Ulfatur Rohmah; Flora Andeina Hidayatus Sholichah; Dhita Ayu Permata Sari; Tutut Nurita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to examine the concept of humanizing education and understand its application in the learning process based on a review of relevant literature. This research uses a literature study method with a narrative literature review approach. Data sources were obtained from scientific journal articles, books, and academic publications related to humanistic education and critical pedagogy published in 2020–2026. Data collection techniques were carried out through literature searches and selection, while data analysis was carried out descriptively by identifying themes, comparing research results, and conducting synthesis. The results of the study indicate that humanizing education encompasses three main themes: education as a process of humanizing humans, the application of humanistic theory in learning, and critical pedagogy. The synthesis shows that humanistic education positions students as active subjects, encourages critical thinking, and develops potential comprehensively.